In those terrible days : writings from the Lodz Ghetto - Zelkowicz, Josef 1897-1944 (Yad Vashem, 2002)
Josef Zelkowicz was a mainstay of the Lodz Ghetto archives that began to operate in Nov. 1940. This book includes his articles on ghetto life, and sections of his diary